Ultrasound-guided Erector Spinae Plane Block versus Oblique Subcostal Transversus Abdominis Plane Block for Postoperative Analgesia in Laparoscopic Cholecystectomy: A Prospective Observational Study - Wasim Mohammad Bhat; Suhaila Johar; Mariyah Riyaz; Masrat Jan; Hina Khurshid; Rohey Jan; Shazia Bashir; Nazir Ahmad Parray (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Introduction: Postoperative pain following laparoscopic cholecystectomy is multifactorial and requires effective management to enhance recovery and reduce opioid consumption. Ultrasound-guided regional techniques like Erector Spinae Plane Block (ESPB) and Oblique Subcostal Transversus Abdominis Plane (OSTAP) block are increasingly used for postoperative analgesia. Aim: To compare the analgesic efficacy of ESPB and OSTAP block in patients undergoing laparoscopic cholecystectomy. Materials and Methods: The present prospective observational study was conducted in the Department of Anaesthesia at SKIMS Medical College and Hospital, Srinagar, Jammu and Kashmir, India, from June 2024 to December 2025. A total of 56 patients undergoing elective laparoscopic cholecystectomy under general anaesthesia were enrolled into two equal groups: Group O received bilateral OSTAP block, and Group E received bilateral ESPB. Postoperative pain was assessed using the Numerical Rating Scale (NRS) at predefined intervals up to 24 hours. Time to first rescue analgesia, total analgesic consumption, haemodynamic parameters and complications were also evaluated. The p-value 0.05). OSTAP group had four males and 24 females while ESPB group which had 10 males and 18 females (p-value >0.05). Mean Body Mass Index (BMI) was 22.58±1.20 kg/m2 in the OSTAP group and 22.69±1.00 kg/m2 in the ESPB group (p-value >0.05). OSTAP group had 11 American Society of Anaesthesiologists (ASA) I and 17 ASA II patients whereas ESPB group had 12 ASA I and 16 ASA II patients (p-value >0.05). The ESPB group demonstrated significantly lower NRS scores after extubation, in the recovery, at one hour, nine hours, 12 hours, and 24 hours postoperatively (p-value